The ongoing construction trends in Shaktipithas of Himachal Pradesh-symbols of living religious heritage - Bhandari, Harveen; Kaur, Prabhjot; Ramani Grover, Aruna (International Journal of Engineering and Technology, 2018)
Shaktipithas represent India’s rich cultural heritage. The continuity of functions at these sites further reinstates their significance as    Living Religious Heritage. Their spiritual value is central to hundreds of millions of people who visit them every year. The growing   population, boost in commerce, advancements in construction technology has impacted the construction trends in all spheres and typologies of architecture. Temples, the religious heritage of the country, are being widely affected by this new movement in architecture. These temples were built years ago using characteristic elements from Indian traditional temple styles or regional vernacular elements. With growth in population and rising number of pilgrims, these complexes face shortfall of infrastructure facilities. To accommodate large inflow of pilgrims especially on festivals large scale construction activities are in full swing on these sites. This paper tends to present a thorough insight into the ongoing developments at some popular sites in Himachal Pradesh, India which are in contemporary style using modern methods of construction. It is highly insensitive to the existing character of our religious heritage and deteriorates the built environment. So the need arises to conserve our cultural heritage, take timely measures to make these places sustainable pilgrimage destinations and keep alive their distinct sacred visual impact.